Social Insurance against a Short Life: Ante-Mortem versus Post-Mortem Policies - Gregory Ponthiere (Global Labor Organization (GLO), 2023)
Welfare States do not insure citizens against the risk of premature death, i.e., the risk of having a short life. Using a dynamic OLG model with risky lifetime, this paper compares two insurance devices reducing well-being volatility due to the risk of early death: (i) an ante-mortem age-based statistical discrimination policy that consists of an allowance given to all young adults (including the unidentified adults who will die early); (ii) a post-mortem subsidy on accidental bequests due to early death. Each policy is financed by taxing old-age consumption. Whereas each device can yield full insurance, the youth allowance is shown to imply a higher lifetime well-being at the stationary equilibrium. The marginal utility of consumption exceeding the marginal utility of giving when being dead, the youth allowances system is, despite imperfect targeting, a more effi cient mechanism of insurance against the risk of early death.
Keywords: J10; J17; I31; E21; H55; 330; premature death; mortality risk; social insurance; inheritance; lifecycle models